Physicochemical, osteogenic and corrosion properties of bio-functionalized ZnO thin films: Potential material for biomedical applications - Trino, Luciana D. [UNESP]; Albano, Luiz G.S. [UNESP]; Bronze-Uhle, Erika S. [UNESP]; George, Anne; Mathew, Mathew T.; Lisboa-Filho, Paulo N. [UNESP] (Elsevier, 2018)
Nano-sized zinc oxide (ZnO) is well known for its antibacterial activity and biocompatibility, which make this material a promising candidate to tailor titanium (Ti) implant surfaces. In an optimized scenario, the antibacterial activity of ZnO and its biocompatibility can be envisioned as a good bio-functionalization strategy to increase osteointegration. Thus, in this work, it is proposed that the bio-functionalization of ZnO thin films with dentin matrix protein 1 (DMP1) peptides could function as an apatite crystal nucleator. Ti was coated with ZnO and functionalized with two different spacers, 3-(4-aminophenyl) propionic acid (APPA) or 3-mercaptopropionic acid (MPA) to facilitate binding with DMP1 peptides. Attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS) results confirmed the presence of the peptides on the ZnO thin film surface through characteristic bands related to amine and carboxylic acid groups and by the incidence of N 1 s spectra, respectively. Atomic force microscopy (AFM) images indicated that a more uniform layer of DMP1 peptides is formed in the the presence of the APPA and MPA spacers. In general, the results obtained showed that the bio-functionalized ZnO thin films with APPA spacer, ZnO APPA P sample, presented enhanced wettability (17°), surface energy (72 dyn/cm), with an osteogenic surface and apatite nucleating properties. Furthermore, the electrochemical analysis showed increased corrosion resistance with noble EOCP (−0.13 V), Ecorr (−0.46 V), and Icorr (8.91 ×10−7 A/cm2) values. These findings indicated promising applications of ZnO APPA P in biomedical devices once it can accelerate the osteointegration process and improve the corrosion resistance of implants.
Keywords: Bio-functionalization; Corrosion resistance; Functional materials; Osteogenic peptides; Zinc oxide